Joining Forces: The Role of Collaboration in the Development of Legal Thought - George, Tracey E. (2002)
For every reason to believe that collaboration has been influential... there is a countervailing reason to believe that it has played a minor role in the evolution of legal thought. It may be easy to bring to mind a handful of prominent collaborations, but most law review articles seem to be written by one author (notwithstanding their lengthy acknowledgment footnotes, suggesting that even single-author works are shaped by the insights and input of multiple scholars). And while it is true that legal scholars often collaborate on their practically oriented works, scholarly articles might not be well suited to collaboration